Religiusitas, Dukungan Sosial dan Resiliensi Korban Lumpur Lapindo Sidoarjo - Setiawan, Aris; Pratitis, Niken Titi (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2015)
Abstract. The purpose of this study to examine the relation between religiosity and socialsupport to the resilience of Lapindo Sidoarjo Mudflow victims. Research variables weremeasured using resilience scale, scale of religiosity and social support scale. Subjectswere 60 victims of Lapindo mudflow that are married, age 20-40, and as a native. Datawere analyzed using multiple regression analysis. The results of multiple regressionanalysis showed that the variables religiosity and social support significantly associatedwith resilience (F = 22.863 at p = 0.000). Both variables contributed 44.5% towardsresilience. Separately, religiosity has a positive relationship with resilience (t = 2.439 to p= 0.018). Social support has a significant positive correlation with resilience (t = 4.952 atp = 0.000).Keywords: Religiosity, Social support, Resilience.